2015
DOI: 10.1016/j.neuroscience.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Cold stress protein RBM3 responds to temperature change in an ultra-sensitive manner in young neurons

Abstract: Extremely mild hypothermia to 36.0°C is not thought to appreciably differ clinically from 37.0°C. However, it is possible that 36.0°C stimulates highly sensitive hypothermic signaling mechanism(s) and alters biochemistry. To the best of our knowledge, no such ultra-sensitive pathway/mechanisms have been described. Here we show that cold stress protein RNA Binding motif 3 (RBM3) increases in neuron and astrocyte cultures maintained at 33°C or 36°C for 24 or 48h, compared to 37°C controls. Neurons cultured at 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 54 publications
4
66
1
Order By: Relevance
“…Indeed, recent evidence indicates that even a 1°C reduction in temperature induces neuroprotective signaling cascades in neurons in in vitro systems ( Jackson et al, 2015). However, studies are needed to delineate the specific patients who maximally benefit from hypothermia treatment based on additional considerations, such as severity of injury, organ dysfunction following CA, inflammation, and coadministered medications.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent evidence indicates that even a 1°C reduction in temperature induces neuroprotective signaling cascades in neurons in in vitro systems ( Jackson et al, 2015). However, studies are needed to delineate the specific patients who maximally benefit from hypothermia treatment based on additional considerations, such as severity of injury, organ dysfunction following CA, inflammation, and coadministered medications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, work from our laboratory has suggested that TTM may be producing benefit beyond simply preventing fever. Jackson et al (33) reported that clamping isolated rat primary neurons (day in vitro-6 [DIV-6]) in culture at 36°C for 24 or 48h markedly upregulates RBM-3 vs. normothermia—although not quite to the level seen with exposure of these neurons to 33°C. DIV-6 neurons model many features of newborn neurons (34).…”
Section: Introductionmentioning
confidence: 99%
“…DIV-6 neurons model many features of newborn neurons (34). In contrast, DIV-26 neurons, modeling adult neurons exhibit a much more blunted upregulation of RBM-3 at 36° or 33°C (33). Given that a 1°C reduction in temperature is not believed to produce neuroprotection via mechanisms such as reducing energy demands, our findings suggest that TTM may exert benefit by mechanisms beyond simply preventing fever.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical evidence suggests that reductions of brain temperature by 1°C from 37°C to 36°C may be neuroprotective (Jackson et al, 2015), and that these benefits are not achieved with active normothermia (37°C) (Logue et al, 2007). These data raise concern that the neuroprotective benefits of TTM may be reduced when targeting a core temperature of 36°C, if the unmeasured brain temperature were significantly higher.…”
Section: Introductionmentioning
confidence: 99%